Jellyfish Bioprospecting in the Mediterranean Sea: Antioxidant and Lysozyme-Like Activities from Aurelia coerulea (Cnidaria, Scyphozoa) Extracts - Loredana Stabili (MDPI AG, 2021)
Marine invertebrates represent a vast, untapped source of bioactive compounds. Cnidarians are represented by nearly 10,000 species that contain a complex mixture of venoms, collagen, and other bioactive compounds, including enzymes, oligosaccharides, fatty acids, and lipophilic molecules. Due to their high abundance in coastal waters, several jellyfish taxa may be regarded as candidate targets for the discovery of novel lead molecules and biomaterials and as a potential source of food/feed ingredients. The moon jellyfish Aurelia coerulea is one of the most common jellyfish worldwide and is particularly abundant in sheltered coastal lagoons and marinas of the Mediterranean Sea, where it first appeared—as an alien species—in the last century, when Pacific oyster cultivation began. In the present study, the antioxidant and lysozyme antibacterial activities associated with extracts from different medusa compartments—namely the umbrella, oral arms, and secreted mucus—were investigated. Extracts from the oral arms of A. coerulea displayed significant antioxidant activity. Similarly, lysozyme-like activity was the highest in extracts from oral arms. These findings suggest that A. coerulea outbreaks may be used in the search for novel cytolytic and cytotoxic products against marine bacteria. The geographically wide occurrence and the seasonally high abundance of A. coerulea populations in coastal waters envisage and stimulate the search for biotechnological applications of jellyfish biomasses in the pharmaceutical, nutritional, and nutraceutical sectors.